2010
DOI: 10.1021/pr100219y
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin−Proteasome Pathway Is Important for Dengue Virus Infection in Primary Human Endothelial Cells

Abstract: Dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS) are the most severe forms of dengue virus infection with hemorrhage and plasma leakage. However, pathogenic mechanisms of DHF and DSS remain poorly understood. We therefore investigated host responses as determined by changes in the cellular proteome of primary human endothelial cells upon infection with dengue virus serotype 2 (DEN-2) at a multiplicity of infection (MOI) of 10 for 24 h. Two-dimensional PAGE and quantitative intensity analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 50 publications
8
62
0
Order By: Relevance
“…Accumulating evidence has shown that UPS is involved in numerous cellular activities, such as cell cycle control, apoptosis, and immune responses (Choudhury et al, 2013;Rastogi and Mishra, 2012;Tu et al, 2012). It has been demonstrated that UPS is important for the replication of positive-stranded RNA viruses such as CVB3, hepatitis E virus, and dengue virus (Kanlaya et al, 2010;Karpe and Meng, 2012;Si et al, 2007). In the present study, we demonstrated that EV71 infection promoted ubiquitination, while the activity of proteasome remained unchanged.…”
Section: Discussionsupporting
confidence: 61%
“…Accumulating evidence has shown that UPS is involved in numerous cellular activities, such as cell cycle control, apoptosis, and immune responses (Choudhury et al, 2013;Rastogi and Mishra, 2012;Tu et al, 2012). It has been demonstrated that UPS is important for the replication of positive-stranded RNA viruses such as CVB3, hepatitis E virus, and dengue virus (Kanlaya et al, 2010;Karpe and Meng, 2012;Si et al, 2007). In the present study, we demonstrated that EV71 infection promoted ubiquitination, while the activity of proteasome remained unchanged.…”
Section: Discussionsupporting
confidence: 61%
“…The ubiquitin-proteasome pathway is a major regulator of intracellular protein levels and plays an important role in viral infections through the avoidance of host immune surveillance, viral progeny release and budding, transcriptional regulation of the virus, and suppression of apoptosis (17,25). We observed that genes related to the ubiquitin-proteasome pathway were upregulated throughout the course of the infection (Table 2; see also Table S5 in the supplemental material).…”
Section: Discussionmentioning
confidence: 85%
“…The ubiquitin ligase CBLL1 and the ubiquitin/proteasome pathway are thought to be essential for West Nile virus replication (38,39), whereas ubiquitylation of JEV NS3 and NS5 results in viral protein degradation (21). Previously, it was observed that inhibitors of the cellular ubiquitylation could dramatically decrease DENV replication (40). However, the target(s) of ubiquitylation and the underlying molecular mechanisms of why inhibition of ubiquitylation affects DENV replication were largely unknown.…”
Section: Discussionmentioning
confidence: 99%